Rani in the Mermaid Lagoon - Papademetriou, Lisa; Disney Storybook Artists (New York : Random House, 2006)
Since cutting off her wings to save Never Land, Rani, a water-talent fairy, feels out of place with the fairies and wonders if she should live with the mermaids instead
"A Stepping Stone book."
Keywords: Self-esteem -- Fiction; Fairies -- Fiction; Mermaids -- Fiction